Analisis Retorika dalam Tafsir Shafwah Al-Tafasir Terhadap Surah Al-Bayyinah - Fuad Salim; Abuzar Alghifari; Beko Hendro (JOM, 2024)
One of the main characteristics of the Qur'an is its captivating and impactful language that communicates its messages deeply to the listeners' souls. To explore and elucidate this dimension, scholars utilize a discipline known as the Science of Rhetoric (Ilmu Balaghah). Therefore, the author is interested in exploring the message of Surah Al-Bayyinah through the lens of Ilmu Balaghah to uncover the beauty and depth of meaning it contains. Consequently, this research will focus on two aspects: firstly, identifying the rhetorical styles present in Surah Al-Bayyinah; secondly, examining the implications of employing rhetorical styles in interpreting Surah Al-Bayyinah. Furthermore, this study is a literature review (library research) using a qualitative method. The research findings indicate that: 1) Surah Al-Bayyinah contains various rhetorical styles. Ash-Shabuni in his book "Shafwah al-Tafasir" delineates the rhetorical elements in Surah Al-Bayyinah, identifying at least five elements, namely: Ijmal tsumma tafshil, Ath-Thibaq, Muqobalah, Isti'arah tashrihiyyah, Tawafiq al fawashil; 2) The implications of the rhetorical dimension in interpreting Surah Al-Bayyinah have an influence and impact on the conveyed meaning. Each verse containing rhetorical elements in Surah Al-Bayyinah implies the interpreted meaning, and rhetoric serves as a tool to facilitate understanding the hidden meanings behind each of its verses.